Nurul Wahidah and Noraisah Nurul Fatwa Named Winners of AAU - Nur Hartini, Mohd Hatta (UMPSA, 2023)
KUANTAN, 3 October 2023 - Nurul Wahidah Arshad and Noraisah Nurul Fatwa Mohd Razali have been named winners of the 2022 University Academic Award (AAU) at the Scholarly Excellence Awards '22 ceremony held by Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) at the Grand Darul Makmur Hotel, Kuantan recently.